The Effect of Social Media Marketing and Its Indicators on Customer Engagement on Magang Update (Study on followers of the Instagram account @magangupdate on Jabodetabek) - Mashliha Ulya El Madinta; Mimin Aminah (Budapest International Research and Critics University, 2022)
Advances in technology and the internet have improved the standard of living of people in Indonesia and around the world. The purpose of this research is to see how the Instagram Magang Update account utilizes social media marketing. Data for this study was collected between July and November 2021, and includes both quantitative and qualitative data. Respondents in Jabodetabek who follow the Instagram Magang Update social media account are given an online questionnaire to fill out. Descriptive statistical data analysis and Partial Least Square SEM were used in this study. According to the findings of the SEM-PLS research, social media marketing has a direct positive and significant influence on customer engagement. This shows that the more effective social media marketing, the higher the level of customer engagement on the Instagram Magang Update account.